Mixing QE and interest rate policies at the effective lower bound: Micro evidence from the euro area - Christian Bittner; Alexander Rodnyansky; Farzad Saidi; Yannick Timmer (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2024)
We study the interaction of expansionary rate-based monetary policy and quantitative easing, despite their concurrent implementation, by exploiting heterogeneous banks and the introduction of negative monetary-policy rates in a fragmented euro area. Quantitative easing increases credit supply less, translating into weaker employment growth, when banks' funding costs do not decrease. Using administrative data from Germany, we uncover that among banks selling their securities, central-bank reserves remain disproportionately with high-deposit banks that are constrained due to sticky customer deposits at the zero lower bound. Affected German banks lend relatively less to ffrms while increasing their interbank exposure in the euro area.
Keywords: E44; E52; E58; E63; F45; G20; G21; 330; Negative Interest Rates; Quantitative Easing; Unconventional Monetary Policy; Bank Lending Channel